SPATIAL AND TEMPORAL VARIABILITY OF TEMPERATURE AND PRECIPITATION IN THE DEBED RIVER BASIN (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The main patterns of spatial and temporal variability of air temperature and precipitation in Debed River basin (Armenia) for the period of 1963–2020 using daily actual data of the Center for Hydrometeorology and Monitoring SNCO of the Republic of Armenia for the last 58 years for 6 meteorological stations are analyzed and evaluated. The accomplished analysis considered changes in average annual air temperature and atmospheric precipitation for the entire territory of Debed River basin and for each of currently operating meteorological station separately. A map of distribution of long-term average annual temperatures and precipitation in Debed River basin from 1963 to 2020 was made. The entire period of measurements according to the nature of temperature measurement is conditionally divided into two periods: 1963–1992 and 1993–2020. Two time intervals with different trends of changes of annual precipitation were distinguished: 1963–2001 and 2002–2020. Based on the analysis of the results of long-term observations of meteorological stations in Debed River valley relevant data on the spatial and temporal variability of temperature and precipitation from 1963 up to date were received. It has been shown that from 1963 to 2020 air temperature increased by 1.76℃ in average. After 1990, the temperature increased by 0.39℃ for 10 years. Abnormally high temperatures recorded in 1966, 2010 and 2020. Along with temperature increase, there is a stable and fixed tend of precipitation decrease in the most of stations: about 90 mm for 10 years in average, which contributes to the strengthening aridity of the region. Significant impact on precipitation change is caused by the topography of the area, which leads to significant spatial heterogeneity of precipitation. As a result of the research, a significant spatial heterogeneity in the distribution of temperature and precipitation in Debed River basin, as well as a steady growth of average annual temperature and precipitation decrease was revealed, indicating increasing aridity in the region. Therefore, it is necessary to develop programs of measures aimed to reducing the negative consequencesof these changes to ensure future sustainable economic development of the region.
Keywords: Debed River basin; air temperature; precipitation; long-term variability